2015
DOI: 10.5713/ajas.15.0664
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation of Red Ginseng By-product on Laying Performance, Blood Biochemistry, Serum Immunoglobulin and Microbial Population in Laying Hens

Abstract: This study was carried out to investigate the effect of dietary supplementation of red ginseng by-product (RGB) on the laying performance, blood biochemistry, and microbial population in laying hens. A total of 120 Hy-Line Brown laying hens (75 weeks old) were randomly allotted to 1 of 3 dietary treatments with 4 replicates per treatment. A commercial-type basal diet was prepared, and 2 additional diets were prepared by supplementing 5.0 or 10.0 g/kg of RGB to the basal diet at the expense of corn. The diets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
3
15
1
1
Order By: Relevance
“…The presented results for growing broilers show that, compared with no supplementation and the betaine positive control, ginseng extract improved body weight gain by ameliorating FCR under heat stress. Previous results describing the effect of ginseng extract on laying hens and weaned piglets are consistent with our findings [29,30]. Dietary supplementation of a red ginseng by-product significantly increased hen-day egg production, numerically increased egg weight and improved FCR [29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The presented results for growing broilers show that, compared with no supplementation and the betaine positive control, ginseng extract improved body weight gain by ameliorating FCR under heat stress. Previous results describing the effect of ginseng extract on laying hens and weaned piglets are consistent with our findings [29,30]. Dietary supplementation of a red ginseng by-product significantly increased hen-day egg production, numerically increased egg weight and improved FCR [29].…”
Section: Discussionsupporting
confidence: 92%
“…Previous results describing the effect of ginseng extract on laying hens and weaned piglets are consistent with our findings [29,30]. Dietary supplementation of a red ginseng by-product significantly increased hen-day egg production, numerically increased egg weight and improved FCR [29]. Yang et al reported significantly higher final body weight, a better feed utilization rate, and a lower incidence of diarrhea in weaned piglets fed ginseng polysaccharides than in control piglets [30].…”
Section: Discussionsupporting
confidence: 91%
“…The ginseng meal residue contains 16.06% crude protein (CP), 2.0% ether extract (EE), 45% neutral detergent fiber (NDF), and 60% nitrogen-free extract on a dry matter (DM) basis [3]. It also contains saponins, ginsenosides, essential oils, peptides, vitamins, and polysaccharides [7], and studies have revealed an improvement in the milk yield and milk composition of dairy cows [1] and improved the egg production in laying hens [8] that were fed the residue. Replacement of alfalfa hay (0%-15%) with ginseng meal showed that in vitro DM digestibility (IVDMD) was not affected, but CP digestibility decreased without affecting the production of volatile fatty acids (VFAs), indicating that ginseng meal could be used as a ruminant feed resource.…”
Section: Introductionmentioning
confidence: 99%
“…In the livestock industry, the use of food byproducts is of great interest, especially if it pertains to a reduction in feed costs [9]. A large proportion of red ginseng byproduct (RGP) is continuously being produced as the market for red ginseng continues to expand in Korea, but most of it is wasted [7]. To the best of our knowledge, this is the first study to explore the potential of RGP as a protein feed resource for ruminant diets.…”
Section: Introductionmentioning
confidence: 99%
“…Red ginseng contains a variety of other physiologically active compounds such as phenolic compounds, polyacetylenes, peptides, essential oils, and acidic polysaccharides (Lim, Lee, Dong, & Lee, ). As a result of red ginseng production, about 8,000 tons of by‐product are produced (Kang, Park, & Kim, ) and there will be many functional materials in the by‐product that are discarded. A functional material produced from this by‐product would have the potential for extremely high‐added value.…”
Section: Introductionmentioning
confidence: 99%